Peran Seorang Muslim dalam Kehidupan - Syifa Luthfia; Annisa Nur Fajra; Yolanda Kurnia (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2022)
As a caliph on this earth, a Muslim has a role for his environment. Not only amar ma`ruf nahi mungkar (call to goodness and prevent evil), but also many roles that will be played as Muslims. Prevention of munkar is a preventive action, namely an effort to always anticipate various problems that may occur and work hard to prevent them. Inviting good deeds is a curative action that can help individuals solve the problems they face. Helping the oppressed and oppressed is a conservative measure that helps individuals maintain original problematic situations and conditions to resolve. Lastly, the role of Muslims is that the practice and development of religion is a developmental behavior, which helps individuals develop better situations and conditions and can overcome their own problems.